Freshwater Prawn Management System - Selver Raju, Megala; Nureize Arbaiy (Applied Information Technology And Computer Science, 2025)
Prawn farming is an important part of the aquaculture sector that helps meet the growing demand for seafood around the world. Prawn farms can have complicated data management, though. Manual data management, including keeping handwritten documents, is inefficient and can lead to data loss. It can also cause errors. A web-based platform named the Farming Freshwater Prawn Management System has been built to address these issues and boost organisational effectiveness. Prototype models are used in this project. PHP, HTML, and CSS are the programming languages utilised in its development, and Xampp and MySQL are its server and database, respectively. The system offers an improved method for handling farming data in terms of accessibility, accuracy, and efficiency. By removing the possibility of data loss, lowering errors and inconsistencies, and facilitating thorough data analysis and reporting, it increases the operational efficacy of prawn farming.